A robust and multi chaotic DNA image encryption with pixel-value pseudorandom substitution scheme - Dong, Wenlong; Li, Qiliang; Tang, Yiwen; Hu, Miao; Zeng, Ran (Optics communications, 2021)
A color image DNA encryption system, based on multi optical chaos and pixel-value pseudorandom substitution, is proposed. In the scheme, four twin-slave-laser-pairs (TSLPs) subject to the optical injection from the chaotic master laser (ML) generate the four respectively synchronized chaotic signals. Three of these signals are used to generate keys, which are performed DNA operations with three components of color image, and the rest chaotic signals are utilized to control the choice of styles of DNA operations. The proposed image encryption algorithm includes pixel-value pseudorandom substitution based on global bit scrambling and image diffusion based on DNA encryption. After the group velocity dispersion (GVD) inside 50 km long SMF is compensated by a 1 km long DCF, the data can be well recovered at receiving end. The research results highlight that our cipher system can well achieve the encryption and decryption of color image, and is effective and highly secure to resist a variety of attacks by analyzing the randomness, key sensitivity, statistical feature, information entropy, differential performance, noise effect, PSNR and MSE of image in encryption and decryption process. The scheme is promising for color image encryption application in optical communication. •A main laser drives four twin slaver laser pairs to generate optical chaos with high complexity.•Multi optical chaos is used to scramble and diffuse color image.•DNA diffusion algorithm and multiple DNA operations is used to encrypt image.•The group velocity dispersion (GVD) effect in fiber link is considered in transmission of image data.